Prevalence of intestinal parasites and the absence of soil-transmitted helminths in Añatuya, Santiago del Estero, Argentina - Periago, Maria Victoria (2018)
Background: Intestinal parasites (IP) have been reported in point studies from different provinces of Argentina. The presence of soil-transmitted helminths (STH) was detected in many of these studies, including varied prevalences of all five species of STH in the north were the climate is more appropriate for transmission. Nonetheless, Argentina lacks a comprehensive prevalence map of STH. Therefore, the objective of this study was to determine the prevalence of intestinal parasites, focusing on STH, in rural and peri-urban areas of Añatuya, Santiago del Estero Province and identifying risk factors for their transmission. Methods: We conducted a cross-sectional survey in the entire population of three rural lots located on the outskirts of the city between March and June of 2015 and among children in a peri-urban neighbourhood of Añatuya city in July 2016. Socio-economic variables, characteristics of the house and stool samples were collected from each household. Results: A total of 470 stool samples were analysed. The prevalence of STH was extremely low, with only 2 people being positive for hookworm and no detection of other STH. The prevalence of IP was 11.7% for protozoans and 11.1% for helminths. IP were significantly more prevalent in pre-school and school-aged children than in adults (P < 0.05). The level of education of adults was also significantly associated with infection (P = 0.001), as well as the practice of informal slaughter of animals (P = 0.002) and the presence of unimproved walls (P = 0.046) and unimproved floors (P = 0.021) in the household. Nonetheless, the only significant predictors of IP in the logistic regression analysis were age (P < 0.001) and main source of electricity (P = 0.026). Conclusions: The total prevalence of intestinal parasites in the study population was 22.6%. The intestinal parasites detected are transmitted mostly through water (Giardia lamblia) and close contact (Hymenolepis nana), evidencing the need to improve quality control in water facilities and access to improved sanitation to avoid contamination of stored water. The presence of IP was significantly associated with age (with children being more susceptible), households containing unimproved walls and those that did not have access to an electricity network.